P279 The Female Disadvantage in UK CF Registry Data 2008–2013. (12th November 2015) - Hippolyte, S; Keogh, R; MacNeill, S; Simmonds, N; Griesenbach, U
Abstract : Introduction and objectives: The UK Cystic Fibrosis (CF) registry has been in its current form since 2006 offering annual review data comprising of detailed demographic and clinical information on 99% of the UK CF population (>10, 000 individuals). Whilst widely accepted that FEV1 and BMI are well-validated predictors of disease severity and outcome, the role of gender in CF remains debated. In some studies Pseudomonas aeruginosa (PsA) infection occurred earlier in females with a resulting deterioration in FEV1 . Here, we use CF registry data (2008–2013) to assess whether a female disadvantage in FEV1 or BMI exists in the UK population and whether PsA status differs by gender. This is the most complete UK CF registry gender-based analysis to date. Methods and results: Cross-sectional analysis of data from 2010 and 2013 supported decreased female survival (decreasing female prevalence with sequential age groups; 2013 p = 0.0001). It also highlighted lower BMI percentiles and more underweight (BMI <19) individuals amongst females (21.9%; males 13.6%: p = <0.0001), even when adjusted for lung function. Females had worse lung function compared to males, particularly in adolescence; (females: mean FEV1 71.3% at 16–19 yrs (CI 69.2–73.4), males: 78.9% (CI 76.9–81.0); p < 0.0001). Females had higher absolute rates (57.1% on any intravenous antibiotics; 44.8% males) and greater total duration of intravenous antibiotic use across all adult age groups (p <). Females had higher rates of CF-related diabetes from 16–29 years (females 28.2%, males 17.7%: p < 0.005), itself independently associated with worse prognosis. On full analysis from 2008–2013 the age at which chronic PsA was first reported occurred earlier in females (mean 15.5 yrs 95% CI 14.9–16.1) than males (16.7 yrs; 95% CI 16.1–17.3) p = 0.01. Conclusions: Disease severity appears worse in CF females compared to males on cross-sectional analysis of data from 2010 and 2013. Females have earlier PsA infection and lower BMI, both of which are individually associated with worse outcomes and increased intravenous antibiotic use. Females also have reduced lung function, and receive more treatment. These data suggest a persistent and measurable gender difference in the UK CF population which we aim to explore more closely in longitudinal analysis.